Proceedings of the Ocean Drilling Program 1997
DOI: 10.2973/odp.proc.sr.153.033.1997
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-isotope constraints on serpentinization processes in ultramafic rocks from the Mid-Atlantic Ridge (23°N)

Abstract: Früh-Green et al. (1996), we calculate serpentinization temperatures ranging between 430° and 590°C. However, a sensitivity analysis shows that large errors affect these temperatures (about ±100°C). Nevertheless, we think we can determine that the serpentinization occurred at temperatures higher than 350°C.Using the mass-balance equation developed by Taylor (1977), and assuming that seawater (δ 18 θ = Woo) or 18 O hydrothermally enriched seawater (δ 18 θ = +2.4%c) is the serpentinizing fluid, we can determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…Zhao et al (2006) and Beard et al (2009) investigated the formation of mesh-textured magnetite, and suggested that serpentinization takes places at T<200C based on oxygen-isotope geothermometry results (Agrinier et al, 1996;Bach et al, 2004). However, previous studies on serpentinites recovered from the Kane Fracture Zone, Mid-Atlantic Ridge, proposed a complex metamorphic evolution path including hightemperature (>300-400C) serpentinization (Agrinier et al, 1997) which is in agreement with the results of ODP Sites 670 and 920 (Mével, 2003).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Zhao et al (2006) and Beard et al (2009) investigated the formation of mesh-textured magnetite, and suggested that serpentinization takes places at T<200C based on oxygen-isotope geothermometry results (Agrinier et al, 1996;Bach et al, 2004). However, previous studies on serpentinites recovered from the Kane Fracture Zone, Mid-Atlantic Ridge, proposed a complex metamorphic evolution path including hightemperature (>300-400C) serpentinization (Agrinier et al, 1997) which is in agreement with the results of ODP Sites 670 and 920 (Mével, 2003).…”
supporting
confidence: 83%
“…In our samples, intervals of moderately serpentinized peridotites in the upper part of the hole commonly have a reddish color which reflects later oxidation. Oxygen isotopic compositions of serpentine-magnetite pairs in these intervals correspond to relatively low temperatures (<200°C) (Agrinier et al, 1997). By contrast, serpentinites in the lower parts of the two holes are dark green, and the oxygen isotopic compositions are typical of high-temperature serpentinization (>350°C).…”
Section: Figurementioning
confidence: 97%
“…Although few data exist to establish unambiguously W/R for oceanic serpentinites, the limited data that do exist suggest values of approximately unity for relatively high-temperature serpentinites from the Mid-Atlantic Ridge (Agrinier and Cannat, 1997), and values considerably higher than this for serpentinites having formed at lower temperatures (Bonatti et al, 1984). According to reaction 1 the minimum W/R for complete serpentinization is approximately 0.3, since values lower than this would fail to provide sufficient water for olivine hydrolysis to proceed to completion, and thus, no fluid would be available for venting.…”
Section: Heat Of Serpentinizationmentioning
confidence: 91%
“…In this regard, our model is diagnostic rather than predictive. A W/R % 1 is indicated by oxygen isotope measurements on serpentine outcropping south of the Kane Fracture Zone (Agrinier and Cannat, 1997). An alternative, prognostic approach would be to incorporate the kinetics of serpentinization as a continuous function of temperature as recently done by Emmanuel and Berkowitz (2006) in a cellular convection model.…”
Section: Model Descriptionmentioning
confidence: 99%